Acknowledgement to Reviewers - ., .; ., . (Journal of Cereal Research, 2019)
The editorial team greatly acknowledge the assistance of reviewers who have dedicated their precious time and expertise to the journal’s grueling editorial process over the past four months, regardless of whether the articles are finally published or not. In special issue of rice in 2019, a total of 17 articles were published in the journal, with a median time to first decision of 24 days and a median time from submission to publication of 65 days. The editors would like to express their sincere gratitude to the reviewers for their unstinting contribution for special issue on rice in Journal of Cereal Research, volume 11, issue 3 in 2019.